AB0094 A Dual Pathomechnism of Local TNF Produceing IGA B Cells in RA Synovial Tissue. (15th July 2016) - Konthur, Z.; Nonhoff, U.; Wiemkes, M.M.; Detert, J.; Braun, T.; Hollidt, J.M.; Burmester, G.R.; Skriner, K.
Abstract : Background: So far no mechanism for non response to biologicals targeting TNFα has been described despite one third of rheumatoid arthritis patients treated are non-responders. Objectives: We investigated the differences in seroreactivity of patients responding and not responding to TNF therapies prior and after therapy and identified diagnostically applicable IgA autoantigenicity set to identify non response. Methods: Screening with patient sera were conducted with 5 different roteins candidates which were identified by protein maroarray screening (Anal Biochem. 1999 May 15;270(1):103–11.9) expressed recombinantly in E. coli, purified and further stratified with a large well defined patient cohort by ELISA. Baseline sera form PREDICT trial treated with Enbrel) and patients treated with Humira in the HIT HARD (Ann Rheum Dis. 2013 Jun;72(6):844–509 trial and 66 baseline sera from Charite in addition treated with (Cimzia, Infiximab) were ivestigated by Pre. mark TNF ELISA from DRDx GmbH. Results: Pretreatment sera from patients with diagnosis of RA based on the ACR classification criteria who were initiated on therapy with TNFalpha inhibitors were analyzed with five markers from the biomarker set of highest priority (RAB11B, PPP2R1A, KPNB1, Cog 4, FTFT1) using an ELISAs assay. In total, analyses of 203 patients were carried out, of which 162 were clearly defined as Responder and 41 were clearly defined as non-Responder after 6 month treatment. 81% of Non-responder could be clearly identified with the pre.markTNF Test. The assay has currently a specificity 94%. Moreover, 80 baseline serum samples from the PREDICT study with Enbrel and 57 baseline sera from an early intervention trial Hit Hard (Ann Rheum Dis. 2013 Jun;72(6):844–509) with Humira were analysed. In early subset, all 3 non-responder were identified and the specificity of the assay was 98%. In the PREDICT study Enbrel non responders were identified with 68.8% sensitivity and a specificity of 92.5%. Moreover 60 patients treated with TNFalpha inhibitors TNF from Stockholm and Vienna have been tested with >90% specificity to predict non response. The amount of IgA produceing B cell in the synovia differs significantly between the patients which is not seen with IgG produceing B cells. Moreover the potent IgA autoantibodies induce high amount of TNF alpha in marophage assay were IgG do not. A dual pathomechnism of local TNF produceing IgA B cells in RA synovial tissue and TNF produceing macrophages is proposed. Conclusions: These data suggest that non-response to anti-TNFα biologicals might be predicted based on frequency and magnitude of autoantibodies to specific IgA autoantigens. SFB can stimulate multiple intestinal homeostatic IgA and TNF induceing B cells might be important for disease persistence in TNFα non responders. Disclosure of Interest: None declared